Microstructural evolution and mechanical behavior of powder metallurgy based SiC/Al–Mg-Sc-Zr nanocomposite subjected to multi-pass friction stir processing - G. Q., Huang; J., Wu; W. T., Hou; L. H., Shah; A. R. H., Midawi; A. P., Gerlich; Y. F., Shen; F. Q., Meng (Elsevier, 2021)
Powder metallurgy (PM) is a versatile technique to fabricate the particulate reinforced aluminum matrix composites (AMCs) by combining Al alloy powders with various types of reinforcement particles. However, the AMCs fabricated by PM generally lack ductility due to processing-related factors such as porosity, oxygen content, and undesirable microstructural features initiated by the contamination during powder preparation or sintering. In this study, the 5 wt% SiC/Al–Mg-Sc-Zr nanocomposite produced by PM was subjected to friction stir processing (FSP) to obtain the dense, uniform and refined microstructures and the attendant improved mechanical properties. The effect of FSP passes on the microstructural features and mechanical properties of as-PM nanocomposite was investigated, and the strengthening and toughening mechanism of FSPed nanocomposite was revealed. The results showed that the FSP passes with the opposite moving direction of FSP tool between the consecutive passes, largely affected the microstructure of the stir zone. Increasing FSP passes significantly reduced the microdefects and homogenized the microstructure. After 4-pass FSP, the whole stir zone consisting of the dense, uniform and refined microstructure, was obtained. This resulted in an increase in yield strength from 92 MPa in the as-PM condition to 161 MPa after 4-pass FSP, and a simultaneous nearly double enhancement in fracture strain from 0.11 to 0.29.